PENGARUH JAM KERJA, BONUS INSENTIF DAN AREA HOTSPOT TERHADAP PENDAPATAN MITRA PENGEMUDI GRAB DI KOTA TULUNGAGUNG - Vamudah Rupbianti (JIMBIEN: JURNAL MAHASISWA MANAJEMEN, BISNIS, ENTREPRENEURSHIP, 2024)
Abstract The Effect of Working Hours, Incentive Bonus, and Hotspot Area on the Income of Grab Driver Partners in Tulungagung City. Working hours, incentive bonus, and hotspot area are crucial factors to consider in the strategy for Grab driver partners. Grab driver partners need to pay attention to their strategy in order to maximize their income. The objective of this research is to examine the influence of working hours, incentive bonus, and hotspot area on the income of Grab driver partners in Tulungagung city. This research employs a quantitative method through multiple linear regression analysis, and the coefficient of determination is calculated using the SPSS application. The research collected data from 52 respondents through questionnaires distributed to Grab driver partners. The variables in the study consist of the independent variables: working hours (X1), incentive bonus (X2), and hotspot area (X3), and the dependent variable: income (Y). The hypothesis testing uses the t-test and the F-test. The t-test indicates that all variables have a significant impact on the income, and the F-test shows that all variables have a positive influence on the income simultaneously. Keywords : Working hours; incentive bonuses; hotspot areas; income Abstrak Pengaruh Jam Kerja, Bonus Insentif, Dan Area Hotspot Terhadap Pendapatan Mitra Pengemudi Grab Di Kota Tulungagung. Jam kerja, bonus insentif dan area hotspot merupakan hal yang harus di perhatikan dalam strategi mitra pengemudi grab.Mitra pengemudi grab harus memperhatikan strateginya dalam bekerja untuk memperoleh pendapatan yang maksimal. Dalam tujuan penelitian ini adalah untuk mengetahui bagaimana pengaruh jam kerja, bonus insentif dan area hotspot terhadap gaji atau pendapatan mitra pengemudi grab yang ada di kota Tulungagung. Penelitian ini menerapkan metode kuantitatif melalui analisis regresi linier berganda, dan koefisien determinasi dengan cara perhitungan menggunakan aplikasi SPSS. Penelitian mengambil penyebaran data 52 responden dari hasil kuesioner mitra pengemudi grab. Variabel dalam penelitian variabel independen Jam kerja (X1), bonus insentif (X2), dan area hotspot (X3) dan variabel dependen pendapatan (Y). Uji hipotesis menggunakan uji t dan uji f. Uji t semua variabel mempunyai pengaruh signifikan terhadap gaji atau pendapatan dan secara simultan uji f semua variabel berpengaruh positif terhadap pendapatan. Kata kunci: Jam kerja; bonus insentif; area hotspot; pendapatan